Difference between revisions of "Side Proof 5"

From Polymath1Wiki
Jump to: navigation, search
 
Line 64: Line 64:
 
f[411,418] = -5-f(139), so f(139)=-1. f[139,154] = -6+f(149)+f(151), so f(149)=f(151)=1. However, now f[295,302] = 6, which forces the discrepancy above 3.
 
f[411,418] = -5-f(139), so f(139)=-1. f[139,154] = -6+f(149)+f(151), so f(149)=f(151)=1. However, now f[295,302] = 6, which forces the discrepancy above 3.
  
This completes side proof 5
+
This completes side proof 5. The assumption f(67)=1 fails at 688.

Latest revision as of 01:36, 16 June 2015

This page will handle one of the long cases in the Human proof that completely multiplicative sequences have discrepancy greater than 3, so that the page can be shorter and not have so many long sections. Specifically, this page will take care of the case where we assume: f(2)=f(7)=f(19)=f(67)=1, f(23)=-1.

Proof

s(74)=4+f(71)+f(73), so f(71)=f(73)=1.

We have two equations:

1) f[145,154] = -4+f(149)+f(151) >= -4

2) f[295,304] = 5-f(101)+f(149)+f(151) <= 4

Subtracting (2) from (1) we get:

(1)-(2) = -9+f(101) >= -8, so f(101)=1

Updating the table:

0 1 2 3 4 5 6 7 8 9
0|+ + - + - - + + +   0-9
- - - - + + + - + +   10-19
- - - - - + - - + +   20-29
+ - + + - - + + + +   30-39
- - - + - - - + - +   40-49
+ + - - - + + - + -   50-59
+ - - + + + + + - +   60-69
- - + - + - + - + +   70-79
- + - - - + + - - +   80-89
- - - + + - - ? + -   90-99
+ + + ? - + - ? - ?   100-109
+ - + + - + + - - -   110-119
+ + - + - - + ? + -   120-129
+ ? + + + + - ? + ?   130-139

We have four equations:

1) f[485,514] = -7-f(97)+f(127)-f(163)-f(167)+f(251)+f(257)+f(487)+f(491)+f(499)+f(503)+f(509) >= -4

2) f[251,266] = 7+f(127)+f(131)+f(251)+f(257)+f(263) <= 4

3) f[319,336] = -7-f(107)-f(109)+f(163)+f(167)+f(331) >= -4

4) f[207,218] = -5+f(107)+f(109)+f(211) >= -4

Adding them together like this:

(1)-(2)+(3)+(4)+26: -f(97)-f(131)+f(211)-f(263)+f(331)+f(487)+f(491)+f(499)+f(503)+f(509) >= 10

Therefore: f(97)=f(131)=f(263)=-1, f(211)=f(331)=f(487)=f(491)=f(499)=f(503)=f(509)=1.

f[219,232] = 7+f(223)+f(227)+f(229), so f(223)=f(227)=f(229)=-1. f[681,688] = 6-f(137)+f(683), so f(137)=1 and f(683)=-1. f[125,138] = 5+f(127), so f(127)=-1.

We now have two equations:

1) s(138) = 3+f(103)+f(107)+f(109) <= 2

2) f[207,218] = -4+f(107)+f(109) >= -4

(2)-(1)+7: -f(103) >= 1

Therefore, f(103) = -1.

f[411,418] = -5-f(139), so f(139)=-1. f[139,154] = -6+f(149)+f(151), so f(149)=f(151)=1. However, now f[295,302] = 6, which forces the discrepancy above 3.

This completes side proof 5. The assumption f(67)=1 fails at 688.